Innovations in use of registry data (INOREG) - Tron A. Moger; Olav Amundsen; Trond Tjerbo; Ragnhild Hellesø; Jon Helgheim Holte; Nina Vøllestad (University of Oslo, 2023)
Abstract: In recent years there have been several political initiatives in Norway, requiring more research into how multimorbidity and health care pathways in the municipality affect outcomes such as work participation, hospital admissions, disability and quality of life for patients with chronic diseases. Most of the care is provided outside hospitals and has been difficult to capture in large, registry-based studies. Focusing on two important groups, patients with chronic obstructive pulmonary disease (COPD) and musculoskeletal disorders (MSD), the INOREG project aims to reduce these knowledge gaps. In the paper we present 1) the data that are used in the project, 2) the construction of samples, variables and possible methods for analysis and 3) an example on how the data and methods will be applied.  The project database is constructed from a novel linkage of national health and welfare registries.  The data cover social, primary and specialized care for all COPD and MSD patients in Norway, long-term care data from Oslo and Trondheim municipalities and functioning and quality of life for ca. 2,700 patients treated at physiotherapy clinics in the FYSIOPRIM project. This enables construction of care pathways and outcomes at the individual level from 2008 through 2019. The project will fill knowledge gaps regarding the patterns of care at different levels in the health care system, and the association to outcomes for chronic patient groups. If the project is successful, it will provide improved insight on how to further develop provision and coordination of services to the decision makers, and ideally reduce inequalities in health.